A new tool for assessing the risk of fall in children with severe disability: development of the ALICE scale - Terzoni, S.; Bianchi, L. C.; Ferrara, P.; Di Bari, A.; Destrebecq, A. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. It is known in the literature that the main cause of physical impairment in children with severe disabilities is falling, which can worsen their already compromised condition. There are no specific scales for this population in the literature, neither in Italian nor in other languages. We created and validated a scale for assessing the risk of falling in children with severe disabilities.Study design. Observational prospective study.Methods. We enrolled children (inpatients or day-hospital) admitted to the “Santa Maria Bambina Centre” of the “Fondazione Onlus Sacra Famiglia” in Cesano Boscone, Milan; the Content Validity Index of the Scale was calculated to assess the content validity of a new scale (ALICE). Cronbach’s alpha coefficient (α) was used to examine internal consistency, Spearman’s rho coefficient to test inter-rater reliability. Sensitivity, specificity, positive and negative predictive values were calculated.Results. Out of 48 patients enrolled, 14 fell (29.2%).  The ALICE scale, with cut-off set at 16, showed a sensitivity of 100%, a specificity of 88.2%, a positive predictive value of 77.8% and a negative predictive value of 100%. The Content Validity Index of the Scale (=0.93), inter-rater reliability (rho=0.91, p